Financial Markets and Public Finance in the Transformation Process - Tanzi, Vito (IMF Working Papers; Working Paper, 1992)
The paper surveys the role of financial markets and fiscal institutions in the transformation process going on in Eastern and Central Europe. It highlights (a) the need to create some sort of 'social ecological balance' necessary for the working of a modern market economy; (b) the need to develop appropriate financial institutions that can mobilize savings and allocate them efficiently; and (c) the major reforms necessary in the fiscal area. It also calls attention to the extent to which monetary and fiscal policies overlap in these countries and the implications of that overlapping.